Uncoupling gene activity from chromatin structure: promoter mutations can inactivate transcription of the yeast HSP82 gene without eliminating nucleosome-free regions. - Lee, M S (1992)
DNase I-hypersensitive sites represent "nucleosome-free" regions in chromatin where the underlying DNA sequence is highly accessible to trans-acting proteins. Here we demonstrate that it is possible to uncouple gene activity from hypersensitive site formation. Point or substitution mutations were introduced into the promoter of the yeast chromosomal HSP82 gene, encoding the 83-kDa heat shock protein (HSP), via site-directed integration. Mutating either the TATA box or heat shock element 1 (HSE1) significantly reduced basal and heat-induced transcription while mutating both essentially inactivated expression. Dormant transcription units exhibited arrays of sequence-positioned nucleosomes; nevertheless, the inactivated genes still retained a hypersensitive site within their mutated promoters. In addition, all yeast strains maintained a heat-inducible hypersensitive site at -600 base pairs (bp), while several mutant strains converted a constitutive hypersensitive site at -300 bp into a heat-inducible one. Thus, mutations in cis-acting elements within a promoter can inactivate transcription without eliminating nucleosome-free regions.